Block periodization - A Layman`s explanation - Landon, T. (2013)
Explanation of the concept of "block periodization" in sports training. Periodization is planning training volume and intensity levels for a season so athletes can achieve desired results at specific times by breaking the season into long, medium, and short training cycles.